Outcome of pregnancies in women receiving velaglucerase alfa for Gaucher disease. Issue 4 (26th February 2014) - Elstein, Deborah; Hughes, Derralynn; Goker‐Alpan, Ozlem; Stivel, Miriam; Baris, Hagit N.; Cohen, Ian J.; Granovsky‐Grisaru, Sorina; Samueloff, Arnon; Mehta, Atul; Zimran, Ari
Abstract Aim Pregnancy and delivery are affected by and – in turn – impact signs and symptoms of Gaucher disease (GD). Prior to enzyme replacement therapy (ERT), the reported missed abortions rate was 25%, with worsening of anemia and thrombocytopenia, with increased frequency of post‐partum hemorrhage, puerperal fever and bone crises during pregnancy. ERT with imiglucerase reduced these adverse events. Velaglucerase alfa (VPRIV), an ERT approved commercially in February 2010, had undergone preclinical reproductive toxicity testing and proven to be safe and effective in phase I/II and III clinical trials. The objective of this study was to ascertain pregnancy outcome in women receiving VPRIV. Methods Among records collected from six multinational clinical sites, 21 females (mean age, 32.0 years) with GD received VPRIV. Results There were 25 singleton pregnancies (mean gravidity, 2.7; mean parity, 2.0; mean months VPRIV, 31.2). Two primiparous women suffered three first trimester abortions and one missed abortion occurred in a multigravida female. Live birth rate was 84% (mean gestational age, 39.7 weeks). Mean birthweight was 3234.4 g, with APGAR scores above 9. All but three were vaginal deliveries; elective cesarean sections were performed in two patients with hip arthroplasty and one after previous cesarean. Nine patients received regional analgesia/anesthesia. Post‐partum complications were rare, with only one post‐partum (placental) bleed which resolved without intervention. Mean hemoglobin and platelet counts improved during pregnancy (9.45% and 26.0%, respectively). Conclusion VPRIV is safe for conception and pregnancy with good maternal and neonatal outcomes.